Tom Burns, Elcio Cornelson, Volker Jaeckel, and Luis Gustavo Vieira, eds. War and Literature: Looking Back on 20th Century Armed Conflicts. Stuttgart: Ibidem Verlag, 2014. - Paul R Schue (Studies in 20th & 21st Century Literature, 2016)
Review of Tom Burns, Elcio Cornelson, Volker Jaeckel, and Luis Gustavo Vieira, eds. War and Literature: Looking Back on 20th Century Armed Conflicts. Stuttgart: Ibidem Verlag, 2014.
Keywords: war; literature; 20th century